The Meaning of Sustainability Accounting: An Accountant's Perspective in Practice and Professional Values - Hasruddin; Marwah Yusuf; Yudi Akhmad Sadeli (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This research aims to uncover the meaning of sustainable accounting as experienced and lived by the accountant of the dam construction project within the scope of PT. Nindya Karya. This research uses an interpretive paradigm with Husserl's transcendental phenomenological approach to understand the conscious experience of accountants in interpreting sustainability accounting practices. Data was obtained through in-depth interviews with project accountants and analyzed through a phenomenological reduction process that included the identification of noema, noesis, intentionality, and the essential meaning of experience. The results of the study show that sustainability accounting practices in construction projects are not only understood as a formal reporting mechanism, but as a professional practice that functions to maintain the financial order of projects, bridge the reality of construction work with the representation of figures in financial statements, and integrate social and environmental dimensions through the project budgeting system. Accountants interpret sustainability accounting as a professional compass that helps navigate the tension between the demands of project efficiency and responsibility to society and the environment. Integrity, professional responsibility, and moral awareness of development impacts are key values that shape sustainability accounting practices in the experience of project accountants. This research contributes to the development of sustainability accounting literature by presenting a phenomenological perspective that places accountants as reflective actors in negotiating sustainability values in the midst of infrastructure project dynamics.